Relationship between Particulate Matter (PM10) and Airway Inflammation Measured with Exhaled Nitric Oxide Test in Seoul, Korea - Juwhan Choi; Jae Kyeom Sim; Jee Youn Oh; Young Seok Lee; Gyu Young Hur; Sung Yong Lee; Jae Jeong Shim; Ji-yong Moon; Kyung Hoon Min (Canadian Respiratory Journal)
Purpose. Particulate matter (PM) is increasing every year in Asia. It is not fully understood how the airway is affected when inhaling PM. We investigated the correlation between particulate matter with a diameter of less than 10 μm (PM10) and fractional exhaled nitric oxide (FeNO) to determine whether PM causes airway inflammation. Material and Methods. We analyzed patients who visited our outpatient clinic and tested FeNO from January 2016 to December 2017 at the Korea University Guro Hospital. PM10 data were provided by the government of the Republic of South Korea, and measuring station of PM10 is located 800 meters from the hospital. We analyzed the correlation between PM10 and FeNO by a Pearson correlation analysis and by a multivariate linear regression analysis. To identify the most correlated times, we analyzed the correlation between the FeNO and PM10 daily average from the day of visit to 4 days before visit. Results. FeNO positively correlated with PM10 at two days before hospital visit in the Pearson correlation (Pearson correlation coefficient = 0.057; P-value = 0.023) and in the multivariate linear regression analysis (B = 0.051, P-value = 0.026). If the PM10 increased by 100 μg/m3, the FeNO result was expected to rise to 8.3 ppb in healthy people without respiratory disease. Conclusion. The positive correlation was found in both healthy people and asthmatic patients. Therefore, PM10 can increase airway inflammation.